Peer Counseling as A Strategy for Overcoming Academic Stress and Burnout - Hendar, Kus (Kuras Institute, 2023)
This research seeks to explore and analyze the effectiveness of peer guidance and counseling (Peer Counseling) in addressing academic stress and burnout experienced by final-year students in Metro City. Academic stress, defined as the pressure stemming from academic demands and competition, is a common issue among students, particularly those nearing the end of their studies. Burnout, which often accompanies this stress, manifests in feelings of exhaustion, detachment, and decreased academic performance. Through the method of library research, this study examines how peer counseling can be utilized as a strategy to alleviate these challenges. Peer counseling provides a supportive environment where students can share their experiences, seek advice, and receive emotional support from their peers. The findings of this research suggest that there is a significant relationship between academic stress and burnout, and that peer counseling has the potential to play a key role in mitigating these issues, thus improving students' overall well-being and academic success. Furthermore, this research emphasizes the importance of creating a supportive academic environment that can help students cope with the pressures they face in their final year of study.